THE EFFECT OF FINANCIAL PERFORMANCE ON STOCK PRICE AT PHARMACEUTICAL SUB-SECTOR COMPANY LISTED IN INDONESIA STOCK EXCHANGE - Edhi Asmirantho; Oktiviani Kusumah Somantri (Universitas Pakuan, 2017)
This study aims to determine the effect of likuidity, solvency, activity, profitability and market with Current Ratio (CR), Debt to Equity Ratio (DER), Total Assets Turnover (TATO), Return on Equity (ROE), and Earnings per Share(EPS), as indicators, of the pharmaceutical company listed in Indonesia Stock Exchange during the period 2012-2016 to stock price. The type of research is explanatory survey verification and research technique used is inferential statistic. In addition the analytical method used in this research is regression analysis of panel data, namely, t test, F test, and classical assumption of normality, multicollinearity, heteroscedasticity and autocorrelation tests with E-Views 9. The results showed that in partial EPS significantly effects stock price, while CR, ROE, DER, and TATO had not significantly effect the stock price. Adjusted R square value was 0,5040 which showed that CR, DER, TATO, ROE, and EPS influenced the dependent variable by 50,40%, while the remaining 49,6% was influenced by other variables. It can be conluded that in sub sector pharmaceutical, investors were more concerned about the companys EPS instead of other variables. On the other hand, investors simultaneously concerned the CR, DER, TATO, ROE, and EPS in their investment decision and also other variables which were not included in this research.Keywords: Current Ratio, Debt to Equity Ratio, Total Assets Turnover, Return on Equity, Earning Per Share, Stock Price